Cerebrovascular ultrasound - Hennerici, Michael G.; Meairs, Stephen (Current opinion in neurology, 1999)
Rapid progress in noninvasive ultrasound techniques has resulted in a wide variety of clinical applications for assessment of both extracranial and intracranial arterial diseases. Recent highlights in cerebrovascular ultrasound research include imaging methods for characterization of intracranial aneurysms, use of echocontrast agents for improved evaluation of acute stroke patients and transient response harmonic imaging for depiction of brain perfusion. The important role of transcranial Doppler microembolism detection in carotid endarterectomy has been defined, new approaches to noninvasive Doppler measurement of intracranial pressure are progressing, and the clinical indications for transcranial Doppler monitoring of intracranial vasospasm to prevent secondary stroke have expanded. New functional transcranial Doppler applications, which are complementary to positron emission tomography and functional magnetic resonance imaging studies, are evolving for evaluation of functional recovery after stroke; investigation of perfusion asymmetries during complex spatial tasks; assessment of hemispheric dominance in surgical candidates for epilepsy surgery; and elucidation of temporal patterns of regional neuronal activity. With increasing sophistication of cerebrovascular ultrasound methodology, it is essential that standards for data acquisition and interpretation be established. Three recent consensus meetings have provided detailed recommendations on quantification of carotid artery stenosis, on characterization of carotid artery plaques and on microembolism detection by transcranial Doppler.
Gesehen am 21.07.2022